2001
DOI: 10.1089/08942680152007936
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of the Deposition of Aerosol in the Maxillary Sinuses Using a Plastinated Model

Abstract: In spite of the widespread use of aerosols in respiratory diseases, very few studies have been performed in the field of ear, nose, and throat (ENT) disorders. The conditions for penetration of aerosols inside the sinus cavities are thus still not understood fully. The aim of this study was to investigate the penetration of aerosols inside maxillary sinuses in vitro, using plastinated models. Three plastinated specimens of the nose and sinuses were made from three different corpses. These specimens were valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 5 publications
1
28
0
Order By: Relevance
“…2) because it constitutes the most realistic model. 3,4 The anatomical specimen was obtained from a cadaver donated to the "Laboratoire d'Anatomie de la Faculté de Médecine Jacques Lisfranc (Saint-Etienne, France)." This type of donation is anonymous.…”
Section: Plastinated Nasal Airway Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…2) because it constitutes the most realistic model. 3,4 The anatomical specimen was obtained from a cadaver donated to the "Laboratoire d'Anatomie de la Faculté de Médecine Jacques Lisfranc (Saint-Etienne, France)." This type of donation is anonymous.…”
Section: Plastinated Nasal Airway Modelmentioning
confidence: 99%
“…This type of donation is anonymous. Our plastinated model is the same as "model 2" used in the study by Durand et al 4 Plastination is a well-known technique for anatomical conservation. It consists of extracting water and lipids from biological tissues and then replacing them with curable polymers.…”
Section: Plastinated Nasal Airway Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The boxed region delineates the olfactory region, which is shown in Fig. 2 drugs are best targeted to the middle meatus [33], while the turbinates and septum wall are best for systemic delivery owing to efficient drug absorption [1]. For direct nose-to-CNS transport, the olfactory region is the best target [34].…”
Section: Factors Affecting Deposition and Clearancementioning
confidence: 99%
“…Comparison of the deposition patterns of nebulizers versus nasal sprays has been done [14]. Such studies have shown nebulizers to be capable of covering a greater surface area than nasal sprays cover in normal human volunteers [15].…”
Section: Sinus Nebulizationmentioning
confidence: 99%